Harmonic issues in power syetem and power electronic circuits - Pan, Yunru (2012)
As the development of social civilization, humans cannot live without electricity. In industrial, the electrical power system aims to producing or using “clean power”, which means the output power supply approximately ideal sinusoidal waveform. For over 45 years ago, the most commonly used power supply technology was using standard 50/60 Hz SCR controller and transformer or rectifier sets. But during the recent 10 years, a new power switching strategy had been introduced to power supply industry. This new technology is based on high frequency switch mode supplies. The switching frequency is usually above 1MHz. Besides the advantages of smaller size and lighter weight compared to linear regulators, the most significant beneficial is lower harmonics and lower heat are generated due to higher efficiency. Therefore, this new technology is widely used in industrial companies.